Relatório de estágio curricular supervisionado em medicina veterinária – área: clínica de ruminantes e bovinocultura leiteira - (:unkn) unknown (Universidade Federal do Pampa, 2018)
This supervised internship report on veterinary medicine (ECSMV) Federal University of Pampa (UNIPAMPA), Campus Uruguaiana, aimed at describe the activities developed and cases followed. The internship took place under the guidance of Professor Cláudia Acosta Duarte. The first stage of the internship was carried out in the dairy cattle area, at the Minas Gerais Farm, located in the municipality of Ressaquinha, MG, from January 8 to January 28, 2018 and from March 5 to April 28, 2018, making a total of 400 hours of internship, under the supervision of the Veterinary Doctor Edyslan Pereira Chiericato. During the internship it was possible to follow the routine of a dairy property, in addition to clinical and prophylactic management of animals. The second stage of internship was carried out in the ruminant clinic area, in the bovine clinic sector of Federal Rural University of Pernambuco (UFRPE), Campus Garanhuns, in the period from 01 on February 28, 2018, totaling 140 hours, under the supervision of the Veterinary Physician Maria Isabel de Souza. During the internship period at Clínica de Bovinos de Garanhuns (CBG), it was possible to follow the clinical, surgical and diagnostic routine of the place. ESCMV was carried out over a period of four months, completing a total workload of 536 hours. This report describes the places where the internship takes place, the main activities developed, the description of a case of pregnancy toxemia associated with fibrosis liver disease and a case of bovine thromboembolic pneumonia.
Report of supervised internship in veterinary medicine - area: ruminant clinic and dairy cattle
Keywords: Medicina Veterinária; Bovinocultura; Bovinocultura de leite; Gado leiteiro; Clínica médica veterinária; Clínica Veterinária; Clínica de grandes animais; Ruminantes; Fibrose hepática; Pneumonia tromboembólica em bovinos; Cattle; veterinary Medicine; Dairy Cattle; Veterinary medical clinic; Veterinary clinic; Large Animal Clinic; Ruminants; Hepatic fibrosis; Thromboembolic pneumonia in cattle; CNPQ::CIENCIAS AGRARIAS